1986
DOI: 10.1007/bf01317375
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal Langerhans cells in resistance to herpes simplex virus infection

Abstract: To investigate the role of epidermal Langerhans cells (LC) in resistance to herpes simplex virus (HSV) infection, nonadherent spleen cells taken from BALB/c mice immunized with HSV were cultured with syngeneic epidermal cells (EC) and ultraviolet light-inactivated HSV antigen. After five days of culture, T cell-dependent proliferative response was determined by 3H-thymidine incorporation. Treatment of EC with anti-Iad monoclonal antibody plus complement before cultivation prevented this proliferation, which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
2
26
0
1
Order By: Relevance
“…The observations that nude mice develop more severe blepharitis than normal mice (2) and that depletion of both CD4 ϩ and CD8 ϩ T cells before challenge enhances development of periocular skin lesions (16) suggest that T cells are important in clearance of virus from periocular skin and in limiting disease. Such a role for T cells in clearance from dermal lesions has been reported (32)(33)(34)51). It follows then that mice in which a stronger or more competent immune response has been induced would be able to more effectively prevent development of blepharitis (41).…”
Section: ϫ 10mentioning
confidence: 93%
“…The observations that nude mice develop more severe blepharitis than normal mice (2) and that depletion of both CD4 ϩ and CD8 ϩ T cells before challenge enhances development of periocular skin lesions (16) suggest that T cells are important in clearance of virus from periocular skin and in limiting disease. Such a role for T cells in clearance from dermal lesions has been reported (32)(33)(34)51). It follows then that mice in which a stronger or more competent immune response has been induced would be able to more effectively prevent development of blepharitis (41).…”
Section: ϫ 10mentioning
confidence: 93%
“…It has been shown that Langerhans cells are the major antigen presenting cells for HSV in human epidermis (Vestey et al, 1990) and murine epidermis (Yasumoto et al, 1986), and that the density of Langerhans cells at the site of intradermal inoculation affects the severity of the infection, fewer resulting in greater morbidity (Sprecher & Becker, 1986). UV irradiation is known to have several effects on Langerhans cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an important role for Langerhans cells in host defence against herpes virus infection has been dem onstrated [3][4][5]. Yasumotoet al [3] have discovered that nonadherent spleen cells from mice immunized with her pes simplex virus (HSV) produced no increase in thymi dine uptake when stimulated only by HSV antigen that was inactivated by ultraviolet light. However, addition of synergic epidermal cells to these spleen cells induced a remarkable increase in thymidine uptake.…”
Section: Commentsmentioning
confidence: 99%